A super-weather-resistant anticorrosive coating for a tower drum outer wall and a preparation method thereof

CN122978809APending Publication Date: 2026-10-27IANGSU JINLING SPECIAL PAINT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611454289.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,甘肃大部分区域处于戈壁荒漠中,常年伴有沙尘,提供优异风能的同时,设备持续受到高速风沙冲刷,1-3年就会出现磨损;且甘肃年温差极大,涂料长期处于极端温度交替环境,更易出现脆化、开裂;甘肃地区的紫外强度较高,同时空气极度干燥,造成普通涂料易出现快速老化粉化,导致涂料稳定性变差

Benefits of technology

[0025]1.本发明利用聚多巴胺在惰性的沉淀硫酸钡外表面形成改性,保证沉淀硫酸钡在恶劣环境下始终保持优异的界面连接性,同时,聚硅氧烷改性环氧树脂不仅大幅提升涂料的紫外黄变耐受性,而且能够利用聚硅氧烷链段的自发迁移性,在涂层表面形成致密聚硅氧烷防护层。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of tower outer wall with super-weathering anticorrosive paint and preparation method thereof, the super-weathering anticorrosive paint includes component A and component B, the mass ratio of component A is as follows: polysiloxane modified epoxy resin 5-8 parts, epoxy resin 45-50 parts, oil-soluble phenolic resin 5-8 parts, hexamethoxymethyl melamine resin 5-6 parts, rutile titanium dioxide 8-10 parts, mica iron oxide 10-15 parts, polydopamine modified precipitated barium sulfate 3-5 parts, ultraviolet absorber 0.5-1 part, leveling agent 0.3-0.8 part, defoaming agent 0.2-0.5 part, dispersing agent 1-2 parts, solvent 12-17 parts.The application utilizes the modification of polydopamine on the surface of inert precipitated barium sulfate, ensures that precipitated barium sulfate always maintains excellent interface connectivity in harsh environment, at the same time, polysiloxane modified epoxy resin not only greatly improves the ultraviolet yellowing resistance of coating, but also can form a dense polysiloxane protective layer on the surface of coating by using the spontaneous migration of polysiloxane segment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention pertains to anti-corrosion coatings, specifically relating to an ultra-weather-resistant anti-corrosion coating for the outer wall of towers and its preparation method. Background Technology

[0002] With the increasing global energy demand and the growing scarcity and pollution of fossil fuels, the development and utilization of clean and renewable energy has become a key global energy issue. Wind energy, which uses natural wind to drive generators and convert wind energy into electricity, does not produce greenhouse gases, air pollutants, or wastewater during the power generation process, making it one of the clean and renewable energy sources.

[0003] As the world's largest energy consumer, my country has identified wind energy as a key area for renewable energy development. In some regions with favorable natural conditions, wind energy resources hold immense development potential, particularly in Gansu Province. Gansu boasts a unique geographical location and climate, resulting in a distinct three-dimensional climate. This diverse climate and topography fosters abundant wind energy resources, providing unparalleled natural advantages for wind power generation. However, most of Gansu is situated in the Gobi Desert, constantly experiencing sandstorms. While providing excellent wind energy, equipment is continuously subjected to high-speed sandstorms, leading to wear and tear within 1-3 years. Furthermore, Gansu experiences extreme annual temperature variations, placing coatings in a prolonged environment of extreme temperature fluctuations, making them more prone to embrittlement and cracking. The high UV intensity and extremely dry air in Gansu cause ordinary coatings to age and powder rapidly, resulting in decreased stability. Given these extreme environments, there is currently no market-specific ultra-weather-resistant anti-corrosion coating for tower exteriors. Therefore, Gansu urgently needs an anti-corrosion coating that can maintain long-term stability under high radiation conditions and retain its toughness and integrity under extreme temperature differences and prolonged sandstorms. Summary of the Invention

[0004] To address the problems in the prior art, this invention provides an ultra-weather-resistant and corrosion-resistant coating for the outer wall of towers. It utilizes polydopamine to modify the outer surface of inert precipitated barium sulfate, ensuring that the precipitated barium sulfate maintains excellent interfacial connectivity under harsh environments. At the same time, the polysiloxane-modified epoxy resin not only significantly improves the coating's resistance to ultraviolet yellowing, but also utilizes the spontaneous migration of polysiloxane segments to form a dense polysiloxane protective layer on the coating surface.

[0005] To achieve the above technical objectives, the technical solution of the present invention is as follows:

[0006] A super weather-resistant anti-corrosion coating for the outer wall of a tower comprises component A and component B, wherein the mass ratio of component A to component B is 5-7:1, component B is a curing agent, and the mass ratio of component A is as follows:

[0007] The composition includes: 5-8 parts of polysiloxane-modified epoxy resin, 45-50 parts of epoxy resin, 5-8 parts of oil-soluble phenolic resin, 5-6 parts of hexamethoxymethyl melamine resin, 8-10 parts of rutile titanium dioxide, 10-15 parts of mica iron oxide, 3-5 parts of polydopamine-modified precipitated barium sulfate, 0.5-1 part of ultraviolet absorber, 0.3-0.8 parts of leveling agent, 0.2-0.5 parts of defoamer, 1-2 parts of dispersant, and 12-17 parts of solvent.

[0008] The polysiloxane-modified epoxy resin is obtained by catalytic modification using E-44 epoxy resin as a base and hydroxyl-terminated polydimethylsiloxane as a modifier. This polysiloxane-modified epoxy resin undergoes a dehydration condensation reaction between silanol groups and the active groups of the epoxy resin to obtain a high-performance composite material, overcoming the shortcomings of ordinary epoxy resins such as poor heat resistance and brittleness. The introduction of Si-O-Si bonds into the molecular chain of the polysiloxane-modified epoxy resin forms a stable chemical structure with the epoxy groups, avoiding the problem of phase separation. Simultaneously, the addition of polydimethylsiloxane significantly improves the problem of ultraviolet yellowing, effectively enhancing the temperature and weather resistance of the epoxy resin. The mass ratio of the polysiloxane-modified epoxy resin is: 80-90 parts epoxy resin, 10-20 parts hydroxyl-terminated polydimethylsiloxane, and 0.3-0.5 parts catalyst. The epoxy resin used is E-44 epoxy resin, and the catalyst is dibutyltin dilaurate. The preparation method of the polysiloxane-modified epoxy resin includes the following steps: a1, placing the epoxy resin in a reaction vessel and stirring at a constant temperature until completely melted, then adding the hydroxyl-terminated polydimethylsiloxane and stirring continuously for 30-40 minutes until a uniform mixture is obtained. The constant temperature stirring temperature is 55-60℃, and the stirring speed is 500-800 r / min. / min; the continuous stirring speed is 1000-1500 r / min; a2, the catalyst is added to the reactor under a nitrogen atmosphere and reacted at a constant temperature for 5-6 h to obtain the reactants. The constant temperature reaction temperature is 105-110℃. During the constant temperature reaction, a reflux condenser is used to absorb moisture. This step uses a nitrogen atmosphere instead of an air atmosphere, which can effectively avoid oxidation and yellowing of the system during high-temperature reactions. At the same time, the absorption of moisture products during the constant temperature reaction promotes the forward condensation reaction; a3, the reactor is naturally cooled to below 60℃ to obtain the polysiloxane-modified epoxy resin product with terminal hydroxyl polysiloxane modification. This polysiloxane-modified epoxy resin uses precise control of the amount of terminal hydroxyl polydimethylsiloxane added to accurately control the uniform modification of terminal hydroxyl polysiloxane. Overall, the flexible polysiloxane segments are uniformly distributed as a dispersed phase in the continuous epoxy phase, forming a bicontinuous phase structure. Therefore, the modified epoxy resin retains the strong adhesion and high mechanical strength of epoxy resin, while introducing the low surface energy, high weather resistance, and hydrophobic properties of polysiloxane. In particular, the polysiloxane segments spontaneously migrate to the surface during the coating curing process, constructing a dense polysiloxane-rich layer with low surface energy on the coating surface without affecting the interfacial bonding strength between the coating and the substrate, effectively reducing the probability of adhesion and penetration of corrosive media.

[0009] The epoxy resin used is E-44 epoxy resin.

[0010] The hydroxymethyl or methyl ether hydroxymethyl groups in the oil-soluble phenolic resin can react chemically with the secondary hydroxyl groups on the epoxy resin molecules to form a more complex three-dimensional cross-linking network, which greatly improves the overall cross-linking density of the coating and avoids the problem of insufficient cross-linking in the pure epoxy system, resulting in a soft coating and poor resistance to media penetration. At the same time, the addition of oil-soluble phenolic resin ensures that the coating has better weather resistance and aging resistance, and the rigid benzene ring structure of phenolic resin can form a stable cross-linking network, which greatly enhances thermal stability.

[0011] The hexamethoxymethyl melamine resin is a fully methylated amino resin with six highly active methoxy functional groups. Under heating conditions, it can react with the hydroxyl and carboxyl groups on the epoxy resin to crosslink the originally linear epoxy molecules into a three-dimensional network structure, which greatly improves the density and structural stability of the film. At the same time, the hexamethoxymethyl melamine resin hardly undergoes self-crosslinking reaction under normal construction temperatures and without strong acid catalysts. Almost all active sites can react directionally with the epoxy matrix, avoiding ineffective side reactions.

[0012] The rutile titanium dioxide has a particle size of 0.2-0.3 μm. Rutile titanium dioxide has a relatively concentrated particle size and the highest light scattering efficiency, effectively scattering UVA and UVB ultraviolet rays. This significantly reduces the photodegradation effect of ultraviolet rays on epoxy and other resin matrices, extending the outdoor weather resistance life of the coating and preventing chalking and yellowing due to prolonged exposure to sunlight. Simultaneously, the uniform particle size of the titanium dioxide can form a denser packing structure in the coating, reducing micropores within the coating and extending the penetration path of corrosive media such as water and salt spray, indirectly improving the coating's salt spray resistance.

[0013] The mica iron oxide significantly enhances the long-term anti-corrosion performance of the coating through physical shielding. Its scaly structure forms a layered, parallel arrangement within the coating, creating a dense physical barrier that greatly extends the penetration path of corrosive media such as water vapor, salt spray, and oxygen. Simultaneously, the mica iron oxide exhibits extremely stable chemical properties, showing almost no reaction in acidic, alkaline, or saline environments, preventing side reactions that could damage the cross-linked structure within the coating and ensuring its long-term structural stability. Furthermore, the excellent interfacial affinity between the mica iron oxide and the epoxy resin significantly improves the coating's mechanical strength, enhances its wear resistance and impact resistance, and prevents scratches and cracking during application and use. The outstanding UV shielding capability of the mica iron oxide effectively blocks direct UV radiation to the epoxy resin, significantly reducing the rate of resin photo-aging degradation, improving the coating's outdoor weather resistance, and preventing chalking and yellowing even after prolonged exposure to sunlight.

[0014] The polydopamine-modified precipitated barium sulfate is a polydopamine-encapsulated precipitated barium sulfate, forming a core-shell structure with precipitated barium sulfate as the core and polydopamine as the surface coating. The precipitated barium sulfate is composed of small-particle-size precipitated barium sulfate (0.2-0.4 μm) and large-particle-size precipitated barium sulfate (10-15 μm), with a mass ratio of 6:3-4. The precipitated barium sulfate is uniformly dispersed in the coating, forming high-hardness micro-regions on the surface, significantly enhancing the coating's wear resistance and erosion resistance. The large and small-particle-size precipitated barium sulfate achieve the densest particle packing within the coating, significantly filling the tiny voids inside the coating, extending the penetration path of corrosive media, and significantly improving the coating's salt spray resistance. However, precipitated barium sulfate hardly reacts with materials such as epoxy resin, and does not disrupt the integrity of the epoxy cross-linking network. In other words, the surface of precipitated barium sulfate is highly chemically inert and does not form chemical bonds with the epoxy matrix. This results in tiny air pores at the two-phase interface, which become preferential channels for corrosive media penetration, reducing the coating's shielding and anti-corrosion performance. To address this issue, the surface of precipitated barium sulfate is coated with polydopamine, utilizing the adhesion properties of polydopamine to enhance the surface activity of the precipitated barium sulfate. Polydopamine molecules contain a large number of catechol and amino groups, which can form strong coordination bonds and various physicochemical adhesions with the substrate, significantly improving the internal bonding strength of the coating, thereby ensuring the stability and interfacial connectivity of the precipitated barium sulfate. Simultaneously, the dispersibility of polydopamine-modified precipitated barium sulfate in the coating is greatly improved, constructing a denser barrier structure, extending the penetration path of corrosive media, and exhibiting excellent anti-corrosion performance.The preparation method of polydopamine-modified precipitated barium sulfate includes the following steps: b1, precipitated barium sulfate is placed in an ethanol-water solution and sonicated for 20-30 minutes, filtered, and completely dried to obtain a clean-surfaced precipitated barium sulfate. The volume percentage of ethanol in the ethanol-water solution is 20-30%, the mass ratio of precipitated barium sulfate to the ethanol-water solution is 1:20-25, the ultrasonic frequency is 70-90 kHz, and the temperature is 10-20℃. This step utilizes the solubility and permeability of the ethanol-water solution, combined with the exfoliating properties of ultrasound, to completely remove impurities from the surface of the precipitated barium sulfate, ensuring a clean surface. b2, precipitated barium sulfate is placed in a dopamine hydrochloride solution and stirred for 20-30 minutes, filtered, to obtain a coated precipitated barium sulfate. The concentration of the precipitated barium sulfate in the dopamine hydrochloride solution is 10-30 g / L. The dopamine hydrochloride solution is a dopamine-Tris buffer solution with a pH of 8.5 and a dopamine concentration of 5-8 g / L. In this step, the surface of the precipitated barium sulfate is wetted by water in the dopamine hydrochloride solution, and an alkaline liquid film is formed on the surface of the precipitated barium sulfate by utilizing the adhesiveness of dopamine hydrochloride itself. b3, the coated precipitated barium sulfate is heated and allowed to stand for 2-3 hours to obtain polydopamine-modified precipitated barium sulfate. The heating and standing temperature is 50-60℃. In this step, the constant temperature standing method is used to form an alkaline self-polymerization reaction with the oxygen in the air, thereby ensuring that the dopamine hydrochloride in the liquid film self-polymerizes into polydopamine, thus obtaining polydopamine-encapsulated precipitated barium sulfate.

[0015] The ultraviolet absorber is UV327.

[0016] The leveling agent is BYK-333.

[0017] The defoamer is BYK-066.

[0018] The dispersant is BYK-110.

[0019] The solvent is composed of xylene and n-butanol, and the mass ratio of xylene to n-butanol is 7:3.

[0020] The curing agent is isophorone diamine.

[0021] The preparation method of the ultra-weather-resistant anti-corrosion coating includes the following steps:

[0022] Step 1: Add polysiloxane-modified epoxy resin, epoxy resin, oil-soluble phenolic resin, and hexamethoxymethyl melamine resin to a mixed solvent and stir until homogeneous. Then, add rutile titanium dioxide, mica iron oxide, and polydopamine-modified precipitated barium sulfate sequentially and stir continuously for 20 minutes. Finally, add ultraviolet absorber, leveling agent, defoamer, and dispersant and continue dispersing for 30-40 minutes to obtain component A mixture. The stirring speed for homogeneous mixing is 400-600 r / min, the stirring speed for continuous stirring is 700-1000 r / min, and the stirring speed for dispersion is 1000-1500 r / min.

[0023] Step 2: Rapidly stir the mixture of component B and component A in a certain proportion to obtain an ultra-weather-resistant and corrosion-resistant coating; the stirring speed of the rapid stirring is 1500-2000 r / min.

[0024] As can be seen from the above description, the present invention has the following advantages:

[0025] 1. This invention utilizes polydopamine to modify the outer surface of inert precipitated barium sulfate, ensuring that the precipitated barium sulfate maintains excellent interfacial connectivity under harsh environments. At the same time, the polysiloxane-modified epoxy resin not only significantly improves the UV yellowing resistance of the coating, but also utilizes the spontaneous migration of polysiloxane segments to form a dense polysiloxane protective layer on the coating surface.

[0026] 2. This invention utilizes low-concentration immersion in dopamine hydrochloride and in-situ polymerization in a liquid film system to minimize the impact of polydopamine on the precipitated barium sulfate while improving the activity of surface groups on the precipitated barium sulfate. Detailed Implementation

[0027] The present invention will be described in detail with reference to the embodiments, but the claims of the present invention are not intended to limit the scope of the invention.

[0028] Example 1

[0029] A super weather-resistant anti-corrosion coating for the outer wall of a tower comprises component A and component B, wherein the mass ratio of component A to component B is 5:1, component B is a curing agent, and the mass ratio of component A is:

[0030] The composition includes 5 parts polysiloxane-modified epoxy resin, 45 parts epoxy resin, 5 parts oil-soluble phenolic resin, 5 parts hexamethoxymethyl melamine resin, 8 parts rutile titanium dioxide, 10 parts mica iron oxide, 5 parts polydopamine-modified precipitated barium sulfate, 0.5 parts ultraviolet absorber, 0.8 parts leveling agent, 0.5 parts defoamer, 2 parts dispersant, and 12 parts solvent.

[0031] The polysiloxane-modified epoxy resin is obtained by catalytic modification using E-44 epoxy resin as a base and hydroxyl-terminated polydimethylsiloxane as a modifier. The mass ratio of the polysiloxane-modified epoxy resin is: 90 parts epoxy resin, 10 parts hydroxyl-terminated polydimethylsiloxane, and 0.3 parts catalyst. The epoxy resin used is E-44 epoxy resin, and the catalyst is dibutyltin dilaurate. The preparation method of the polysiloxane-modified epoxy resin includes the following steps: a1, placing the epoxy resin in a reaction vessel and stirring at a constant temperature until completely melted, then adding the hydroxyl-terminated polydimethylsiloxane and stirring continuously for 40 minutes to obtain a uniform mixture. The constant temperature stirring temperature is 60℃, and the stirring speed is 800 r / min; the continuous stirring speed is 1500 r / min; a2, adding the catalyst to the reaction vessel under a nitrogen atmosphere and reacting at a constant temperature for 6 hours to obtain the reactant. The constant temperature reaction temperature is 110℃, and a reflux condenser is used to absorb moisture during the constant temperature reaction; a3, naturally cooling the reaction vessel to 50℃ to obtain the hydroxyl-terminated polysiloxane-modified epoxy resin product.

[0032] The epoxy resin used is E-44 epoxy resin.

[0033] The rutile titanium dioxide has a particle size of 0.2-0.3 μm.

[0034] The polydopamine-modified precipitated barium sulfate is a polydopamine-encapsulated precipitated barium sulfate, forming a core-shell structure with precipitated barium sulfate as the core and polydopamine as the surface coating. The precipitated barium sulfate is composed of small-particle-size precipitated barium sulfate (0.2-0.4 μm) and large-particle-size precipitated barium sulfate (10-15 μm), with a mass ratio of 2:1. The preparation method of the polydopamine-modified precipitated barium sulfate includes the following steps: b1, placing the precipitated barium sulfate in an ethanol-water solution and sonicating for 30 min, filtering, and then completely drying to obtain a clean-surfaced precipitated barium sulfate. The ethanol-water solution contains 20% ethanol by volume, and the mass ratio of the precipitated barium sulfate to the ethanol-water solution is... The ratio was 1:20, the ultrasonic frequency was 90kHz, and the temperature was 20℃; b2, the precipitated barium sulfate was placed in a dopamine hydrochloride solution and stirred for 30min, then filtered to obtain coated precipitated barium sulfate. The concentration of the precipitated barium sulfate in the dopamine hydrochloride solution was 10g / L, the dopamine hydrochloride solution was a dopamine-Tris buffer solution with a pH of 8.5, and the concentration of dopamine hydrochloride was 5g / L; b3, the coated precipitated barium sulfate was heated and allowed to stand for 3h to obtain polydopamine-modified precipitated barium sulfate. The heating and standing temperature was 50℃.

[0035] The ultraviolet absorber is UV327.

[0036] The leveling agent is BYK-333.

[0037] The defoamer is BYK-066.

[0038] The dispersant is BYK-110.

[0039] The solvent is composed of xylene and n-butanol, and the mass ratio of xylene to n-butanol is 7:3.

[0040] The curing agent is isophorone diamine.

[0041] The preparation method of the ultra-weather-resistant anti-corrosion coating includes the following steps:

[0042] Step 1: Polysiloxane-modified epoxy resin, epoxy resin, oil-soluble phenolic resin, and hexamethoxymethyl melamine resin are added to a mixed solvent and stirred until homogeneous. Then, rutile titanium dioxide, mica iron oxide, and polydopamine-modified precipitated barium sulfate are added sequentially and stirred continuously for 20 minutes. Finally, ultraviolet absorber, leveling agent, defoamer, and dispersant are added and dispersion is continued for 40 minutes to obtain component A mixture. The stirring speed for homogeneous mixing is 600 r / min, the stirring speed for continuous mixing is 1000 r / min, and the stirring speed for dispersion is 1500 r / min.

[0043] Step 2: Rapidly stir the mixture of component B and component A in a certain proportion to obtain an ultra-weather-resistant and corrosion-resistant coating; the stirring speed of the rapid stirring is 2000 r / min.

[0044] Example 2

[0045] A super weather-resistant anti-corrosion coating for the outer wall of a tower comprises component A and component B, wherein the mass ratio of component A to component B is 7:1, component B is a curing agent, and the mass ratio of component A is:

[0046] The composition includes 8 parts of polysiloxane-modified epoxy resin, 50 parts of epoxy resin, 8 parts of oil-soluble phenolic resin, 6 parts of hexamethoxymethyl melamine resin, 10 parts of rutile titanium dioxide, 15 parts of mica iron oxide, 3 parts of polydopamine-modified precipitated barium sulfate, 1 part of ultraviolet absorber, 0.3 parts of leveling agent, 0.2 parts of defoamer, 1 part of dispersant, and 17 parts of solvent.

[0047] The polysiloxane-modified epoxy resin is obtained by catalytic modification using E-44 epoxy resin as a base and hydroxyl-terminated polydimethylsiloxane as a modifier. The mass ratio of the polysiloxane-modified epoxy resin is: 80 parts epoxy resin, 20 parts hydroxyl-terminated polydimethylsiloxane, and 0.5 parts catalyst. The epoxy resin used is E-44 epoxy resin, and the catalyst is dibutyltin dilaurate. The preparation method of the polysiloxane-modified epoxy resin includes the following steps: a1, placing the epoxy resin in a reaction vessel and stirring at a constant temperature until completely melted, then adding the hydroxyl-terminated polydimethylsiloxane and stirring continuously for 30 minutes to obtain a uniform mixture. The constant temperature stirring temperature is 55°C, and the stirring speed is 500 r / min; the continuous stirring speed is 1000 r / min; a2, adding the catalyst to the reaction vessel under a nitrogen atmosphere and reacting at a constant temperature for 5 hours to obtain the reactant. The constant temperature reaction temperature is 105°C, and a reflux condenser is used to absorb moisture during the constant temperature reaction; a3, naturally cooling the reaction vessel to 55°C to obtain the hydroxyl-terminated polysiloxane-modified epoxy resin product.

[0048] The epoxy resin used is E-44 epoxy resin.

[0049] The rutile titanium dioxide has a particle size of 0.2-0.3 μm.

[0050] The polydopamine-modified precipitated barium sulfate is a polydopamine-encapsulated precipitated barium sulfate, with precipitated barium sulfate as the core and polydopamine as the surface coating, forming a core-shell structure. The precipitated barium sulfate is composed of small-particle-size precipitated barium sulfate (0.2-0.4 μm) and large-particle-size precipitated barium sulfate (10-15 μm), with a mass ratio of 6:4. The preparation method of the polydopamine-modified precipitated barium sulfate includes the following steps: b1, placing the precipitated barium sulfate in an ethanol-water solution and sonicating for 20 min, filtering, and then completely drying to obtain a clean-surfaced precipitated barium sulfate. The ethanol-water solution contains 30% ethanol by volume, and the mass ratio of the precipitated barium sulfate to the ethanol-water solution is... The ratio was 1:25, the ultrasonic frequency was 70kHz, and the temperature was 10℃; b2, the precipitated barium sulfate was placed in a dopamine hydrochloride solution and stirred for 20min, then filtered to obtain coated precipitated barium sulfate. The concentration of the precipitated barium sulfate in the dopamine hydrochloride solution was 30g / L. The dopamine hydrochloride solution was a dopamine-Tris buffer solution with a pH of 8.5 and a dopamine hydrochloride concentration of 8g / L; b3, the coated precipitated barium sulfate was heated and allowed to stand for 2h to obtain polydopamine-modified precipitated barium sulfate. The heating and standing temperature was 60℃.

[0051] The ultraviolet absorber is UV327.

[0052] The leveling agent is BYK-333.

[0053] The defoamer is BYK-066.

[0054] The dispersant is BYK-110.

[0055] The solvent is composed of xylene and n-butanol, and the mass ratio of xylene to n-butanol is 7:3.

[0056] The curing agent is isophorone diamine.

[0057] The preparation method of the ultra-weather-resistant anti-corrosion coating includes the following steps:

[0058] Step 1: Polysiloxane-modified epoxy resin, epoxy resin, oil-soluble phenolic resin, and hexamethoxymethyl melamine resin are added to a mixed solvent and stirred until homogeneous. Then, rutile titanium dioxide, mica iron oxide, and polydopamine-modified precipitated barium sulfate are added sequentially and stirred continuously for 20 minutes. Finally, ultraviolet absorber, leveling agent, defoamer, and dispersant are added and dispersion is continued for 30 minutes to obtain component A mixture. The stirring speed for homogeneous mixing is 400 r / min, the stirring speed for continuous stirring is 700 r / min, and the stirring speed for dispersion is 1000 r / min.

[0059] Step 2: Rapidly stir the mixture of component B and component A in a certain proportion to obtain an ultra-weather-resistant and corrosion-resistant coating; the stirring speed of the rapid stirring is 1500 r / min.

[0060] Example 3

[0061] A super weather-resistant and anti-corrosion coating for the outer wall of a tower comprises component A and component B, wherein the mass ratio of component A to component B is 6:1, component B is a curing agent, and the mass ratio of component A is:

[0062] The composition includes 7 parts polysiloxane-modified epoxy resin, 48 parts epoxy resin, 6 parts oil-soluble phenolic resin, 6 parts hexamethoxymethyl melamine resin, 9 parts rutile titanium dioxide, 12 parts mica iron oxide, 4 parts polydopamine-modified precipitated barium sulfate, 0.8 parts ultraviolet absorber, 0.5 parts leveling agent, 0.3 parts defoamer, 1 part dispersant, and 15 parts solvent.

[0063] The polysiloxane-modified epoxy resin is obtained by catalytic modification using E-44 epoxy resin as a base and hydroxyl-terminated polydimethylsiloxane as a modifier. The mass ratio of the polysiloxane-modified epoxy resin is: 85 parts epoxy resin, 15 parts hydroxyl-terminated polydimethylsiloxane, and 0.4 parts catalyst. The epoxy resin used is E-44 epoxy resin, and the catalyst is dibutyltin dilaurate. The preparation method of the polysiloxane-modified epoxy resin includes the following steps: a1, placing the epoxy resin in a reaction vessel and stirring at a constant temperature until completely melted, then adding the hydroxyl-terminated polydimethylsiloxane and stirring continuously for 35 minutes to obtain a uniform mixture. The constant temperature stirring temperature is 58℃, and the stirring speed is 600 r / min; the continuous stirring speed is 1200 r / min; a2, adding the catalyst to the reaction vessel under a nitrogen atmosphere and reacting at a constant temperature for 6 hours to obtain the reactant. The constant temperature reaction temperature is 110℃, and a reflux condenser is used to absorb moisture during the constant temperature reaction; a3, naturally cooling the reaction vessel to 55℃ to obtain the hydroxyl-terminated polysiloxane-modified epoxy resin product.

[0064] The epoxy resin used is E-44 epoxy resin.

[0065] The rutile titanium dioxide has a particle size of 0.2-0.3 μm.

[0066] The polydopamine-modified precipitated barium sulfate is a polydopamine-encapsulated precipitated barium sulfate, forming a core-shell structure with precipitated barium sulfate as the core and polydopamine as the surface coating. The precipitated barium sulfate is composed of small-particle-size precipitated barium sulfate (0.2-0.4 μm) and large-particle-size precipitated barium sulfate (10-15 μm), with a mass ratio of 2:1. The preparation method of the polydopamine-modified precipitated barium sulfate includes the following steps: b1, placing the precipitated barium sulfate in an ethanol-water solution and sonicating for 25 min, filtering, and then completely drying to obtain a clean-surfaced precipitated barium sulfate. The ethanol volume percentage in the ethanol-water solution is 25%, and the mass ratio of the precipitated barium sulfate to the ethanol-water solution is... The ratio was 1:23, the ultrasonic frequency was 80kHz, and the temperature was 15℃; b2, the precipitated barium sulfate was placed in a dopamine hydrochloride solution and stirred for 25 minutes, then filtered to obtain coated precipitated barium sulfate. The concentration of the precipitated barium sulfate in the dopamine hydrochloride solution was 20g / L. The dopamine hydrochloride solution was a dopamine-Tris buffer solution with a pH of 8.5 and a dopamine hydrochloride concentration of 7g / L; b3, the coated precipitated barium sulfate was heated and allowed to stand for 3 hours to obtain polydopamine-modified precipitated barium sulfate. The heating and standing temperature was 55℃.

[0067] The ultraviolet absorber is UV327.

[0068] The leveling agent is BYK-333.

[0069] The defoamer is BYK-066.

[0070] The dispersant is BYK-110.

[0071] The solvent is composed of xylene and n-butanol, and the mass ratio of xylene to n-butanol is 7:3.

[0072] The curing agent is isophorone diamine.

[0073] The preparation method of the ultra-weather-resistant anti-corrosion coating includes the following steps:

[0074] Step 1: Polysiloxane-modified epoxy resin, epoxy resin, oil-soluble phenolic resin, and hexamethoxymethyl melamine resin are added to a mixed solvent and stirred until homogeneous. Then, rutile titanium dioxide, mica iron oxide, and polydopamine-modified precipitated barium sulfate are added sequentially and stirred continuously for 20 minutes. Finally, ultraviolet absorber, leveling agent, defoamer, and dispersant are added and dispersion is continued for 35 minutes to obtain component A mixture. The stirring speed for homogeneous mixing is 500 r / min, the stirring speed for continuous stirring is 800 r / min, and the stirring speed for dispersion is 1200 r / min.

[0075] Step 2: Rapidly stir the mixture of component B and component A in a certain proportion to obtain an ultra-weather-resistant and corrosion-resistant coating; the stirring speed of the rapid stirring is 1800 r / min.

[0076] Comparative Example 1

[0077] A super weather-resistant and anti-corrosion coating for the outer wall of a tower comprises component A and component B, wherein the mass ratio of component A to component B is 6:1, component B is a curing agent, and the mass ratio of component A is:

[0078] The composition includes 7 parts polysiloxane-modified epoxy resin, 48 parts epoxy resin, 6 parts oil-soluble phenolic resin, 6 parts hexamethoxymethyl melamine resin, 9 parts rutile titanium dioxide, 12 parts mica iron oxide, 4 parts polydopamine-modified precipitated barium sulfate, 0.8 parts ultraviolet absorber, 0.5 parts leveling agent, 0.3 parts defoamer, 1 part dispersant, and 15 parts solvent.

[0079] The polysiloxane-modified epoxy resin is obtained by catalytic modification using E-44 epoxy resin as a base and hydroxyl-terminated polydimethylsiloxane as a modifier. The mass ratio of the polysiloxane-modified epoxy resin is: 85 parts epoxy resin, 15 parts hydroxyl-terminated polydimethylsiloxane, and 0.4 parts catalyst. The epoxy resin used is E-44 epoxy resin, and the catalyst is dibutyltin dilaurate. The preparation method of the polysiloxane-modified epoxy resin includes the following steps: a1, placing the epoxy resin in a reaction vessel and stirring at a constant temperature until completely melted, then adding the hydroxyl-terminated polydimethylsiloxane and stirring continuously for 35 minutes to obtain a uniform mixture. The constant temperature stirring temperature is 58℃, and the stirring speed is 600 r / min; the continuous stirring speed is 1200 r / min; a2, adding the catalyst to the reaction vessel under a nitrogen atmosphere and reacting at a constant temperature for 6 hours to obtain the reactant. The constant temperature reaction temperature is 110℃, and a reflux condenser is used to absorb moisture during the constant temperature reaction; a3, naturally cooling the reaction vessel to 55℃ to obtain the hydroxyl-terminated polysiloxane-modified epoxy resin product.

[0080] The epoxy resin used is E-44 epoxy resin.

[0081] The rutile titanium dioxide has a particle size of 0.2-0.3 μm.

[0082] The precipitated barium sulfate is composed of small-particle-size precipitated barium sulfate (0.2-0.4 μm) and large-particle-size precipitated barium sulfate (10-15 μm), with a mass ratio of 2:1 between the large-particle-size and small-particle-size precipitated barium sulfate.

[0083] The ultraviolet absorber is UV327.

[0084] The leveling agent is BYK-333.

[0085] The defoamer is BYK-066.

[0086] The dispersant is BYK-110.

[0087] The solvent is composed of xylene and n-butanol, and the mass ratio of xylene to n-butanol is 7:3.

[0088] The curing agent is isophorone diamine.

[0089] The preparation method of the ultra-weather-resistant anti-corrosion coating includes the following steps:

[0090] Step 1: Polysiloxane-modified epoxy resin, epoxy resin, oil-soluble phenolic resin, and hexamethoxymethyl melamine resin are added to a mixed solvent and stirred until homogeneous. Then, rutile titanium dioxide, mica iron oxide, and precipitated barium sulfate are added sequentially and stirred continuously for 20 minutes. Finally, ultraviolet absorber, leveling agent, defoamer, and dispersant are added and the mixture is dispersed for another 35 minutes to obtain component A mixture. The stirring speed for homogeneous mixing is 500 r / min, the stirring speed for continuous mixing is 800 r / min, and the stirring speed for dispersion is 1200 r / min.

[0091] Step 2: Rapidly stir the mixture of component B and component A in a certain proportion to obtain an ultra-weather-resistant and corrosion-resistant coating; the stirring speed of the rapid stirring is 1800 r / min.

[0092] Comparative Example 2

[0093] A super weather-resistant and anti-corrosion coating for the outer wall of a tower comprises component A and component B, wherein the mass ratio of component A to component B is 6:1, component B is a curing agent, and the mass ratio of component A is:

[0094] The composition includes 7 parts polysiloxane-modified epoxy resin, 48 parts epoxy resin, 6 parts oil-soluble phenolic resin, 6 parts hexamethoxymethyl melamine resin, 9 parts rutile titanium dioxide, 12 parts mica iron oxide, 4 parts precipitated barium sulfate, 0.8 parts ultraviolet absorber, 0.5 parts leveling agent, 0.3 parts defoamer, 1 part dispersant, and 15 parts solvent.

[0095] The polysiloxane-modified epoxy resin is obtained by catalytic modification using E-44 epoxy resin as a base and hydroxyl-terminated polydimethylsiloxane as a modifier. The mass ratio of the polysiloxane-modified epoxy resin is: 85 parts epoxy resin, 15 parts hydroxyl-terminated polydimethylsiloxane, and 0.4 parts catalyst. The epoxy resin used is E-44 epoxy resin, and the catalyst is dibutyltin dilaurate. The preparation method of the polysiloxane-modified epoxy resin includes the following steps: a1, placing the epoxy resin in a reaction vessel and stirring at a constant temperature until completely melted, then adding the hydroxyl-terminated polydimethylsiloxane and stirring continuously for 35 minutes to obtain a uniform mixture. The constant temperature stirring temperature is 58℃, and the stirring speed is 600 r / min; the continuous stirring speed is 1200 r / min; a2, adding the catalyst to the reaction vessel under a nitrogen atmosphere and reacting at a constant temperature for 6 hours to obtain the reactant. The constant temperature reaction temperature is 110℃, and a reflux condenser is used to absorb moisture during the constant temperature reaction; a3, naturally cooling the reaction vessel to 55℃ to obtain the hydroxyl-terminated polysiloxane-modified epoxy resin product.

[0096] The epoxy resin used is E-44 epoxy resin.

[0097] The rutile titanium dioxide has a particle size of 0.2-0.3 μm.

[0098] The ultraviolet absorber is UV327.

[0099] The leveling agent is BYK-333.

[0100] The defoamer is BYK-066.

[0101] The dispersant is BYK-110.

[0102] The solvent is composed of xylene and n-butanol, and the mass ratio of xylene to n-butanol is 7:3.

[0103] The curing agent is isophorone diamine.

[0104] The preparation method of the ultra-weather-resistant anti-corrosion coating includes the following steps:

[0105] Step 1: Polysiloxane-modified epoxy resin, epoxy resin, oil-soluble phenolic resin, and hexamethoxymethyl melamine resin are added to a mixed solvent and stirred until homogeneous. Then, rutile titanium dioxide, mica iron oxide, and precipitated barium sulfate are added sequentially and stirred continuously for 20 minutes. Finally, ultraviolet absorber, leveling agent, defoamer, and dispersant are added and the mixture is dispersed for another 35 minutes to obtain component A mixture. The stirring speed for homogeneous mixing is 500 r / min, the stirring speed for continuous mixing is 800 r / min, and the stirring speed for dispersion is 1200 r / min.

[0106] Step 2: Rapidly stir the mixture of component B and component A in a certain proportion to obtain an ultra-weather-resistant and corrosion-resistant coating; the stirring speed of the rapid stirring is 1800 r / min.

[0107] Comparative Example 3

[0108] A super weather-resistant and anti-corrosion coating for the outer wall of a tower comprises component A and component B, wherein the mass ratio of component A to component B is 6:1, component B is a curing agent, and the mass ratio of component A is:

[0109] 55 parts epoxy resin, 6 parts oil-soluble phenolic resin, 6 parts hexamethoxymethyl melamine resin, 9 parts rutile titanium dioxide, 12 parts mica iron oxide, 4 parts precipitated barium sulfate, 0.8 parts ultraviolet absorber, 0.5 parts leveling agent, 0.3 parts defoamer, 1 part dispersant, and 15 parts solvent.

[0110] The epoxy resin used is E-44 epoxy resin.

[0111] The rutile titanium dioxide has a particle size of 0.2-0.3 μm.

[0112] The ultraviolet absorber is UV327.

[0113] The leveling agent is BYK-333.

[0114] The defoamer is BYK-066.

[0115] The dispersant is BYK-110.

[0116] The solvent is composed of xylene and n-butanol, and the mass ratio of xylene to n-butanol is 7:3.

[0117] The curing agent is isophorone diamine.

[0118] The preparation method of the ultra-weather-resistant anti-corrosion coating includes the following steps:

[0119] Step 1: Add epoxy resin, oil-soluble phenolic resin, and hexamethoxymethyl melamine resin to a mixed solvent and stir until homogeneous. Then, add rutile titanium dioxide, mica iron oxide, and precipitated barium sulfate sequentially and stir continuously for 20 minutes. Finally, add UV absorber, leveling agent, defoamer, and dispersant and continue dispersing for 35 minutes to obtain component A mixture. The stirring speed for homogeneous mixing is 500 r / min, the stirring speed for continuous stirring is 800 r / min, and the stirring speed for dispersion is 1200 r / min.

[0120] Step 2: Rapidly stir the mixture of component B and component A in a certain proportion to obtain an ultra-weather-resistant and corrosion-resistant coating; the stirring speed of the rapid stirring is 1800 r / min.

[0121] Performance testing

[0122] Using the coatings of Examples 1-3 and Comparative Examples 1-3 as test samples, they were sprayed onto substrates to form coatings, and the performance of the coatings was tested. The results are as follows:

[0123] Neutral salt spray resistance test: Perform a 1500h neutral salt spray resistance test according to the relevant methods described in GB / T 1771-2007.

[0124] Acid and alkali resistance test: The test was conducted in accordance with the relevant methods described in the international standard ISO 2812-1:2017. The soaking time was 30 days. The alkali solution was sodium hydroxide solution with pH=10 and the acid solution was hydrochloric acid with pH=4.

[0125] Artificial aging resistance test: Perform artificial aging resistance tests for 1500h, 2000h, and 3000h according to the relevant methods in GB / T 1865-2009.

[0126] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Adhesion rating (cross-cut test) Level 1 Level 1 Level 1 Level 1 Level 1 Level 2 Duration of neutral salt spray No blistering, no peeling, no rust No blistering, no peeling, no rust No blistering, no peeling, no rust Very few pores, no shedding A few bubbles, no shedding Obvious air bubbles, with localized peeling skin. Soaking in alkaline solution No bubbling, no cracking No bubbling, no cracking No bubbling, no cracking There are air bubbles and small local cracks. There are bubbles and obvious cracks. Obvious bubbles and cracks acid immersion No bubbling, no cracking No bubbling, no cracking No bubbling, no cracking There are air bubbles and small local cracks. There are bubbles and tiny cracks. Obvious bubbles and cracks 1500h aging resistance No bubbling, no peeling, no powdering No bubbling, no peeling, no powdering No bubbling, no peeling, no powdering No loss of gloss, no fading, no chalking, no cracking Loss of gloss indicates fading, but no chalking or cracking. Significant fading, no powder, obvious cracks 2000h aging resistance No bubbling, no peeling, no powdering No bubbling, no peeling, no powdering No bubbling, no peeling, no powdering Loss of gloss indicates fading, but no chalking or cracking. Loss of gloss includes fading, powdering, and fine cracks. Clearly matte finish, no powder, with localized minor cracks 3000h aging resistance No bubbling, no peeling, no powdering No bubbling, no peeling, no powdering No bubbling, no peeling, no powdering The surface is dull and noticeably faded, without powdering or fine cracks. The surface is dull and noticeably faded, without any chalking or obvious cracking. Noticeably matte finish, contains a small amount of powder, and exhibits obvious cracking.

[0127] The above comparison shows that: this technical solution utilizes polydopamine to modify the surface of inert precipitated barium sulfate, effectively improving the interfacial connectivity of precipitated barium sulfate in anti-corrosion coatings, solving the interfacial crack defects of precipitated barium sulfate, and improving the weather resistance and impermeability of anti-corrosion coatings; at the same time, the combination of large and small particle sizes of precipitated barium sulfate can improve the density of the coating, and with the modification of polydopamine, a dense and ultra-weather-resistant coating is formed; this technical solution utilizes polysiloxane to modify epoxy resin, improving the epoxy resin's resistance to ultraviolet yellowing and also improving the hydrophobicity of its coating. Even though its weather resistance in alkaline solutions is slightly worse than that in acidic systems, it still exhibits excellent anti-corrosion effects.

[0128] It is understood that the above detailed description of the present invention is for illustrative purposes only and is not intended to limit the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that modifications or equivalent substitutions can still be made to the present invention to achieve the same technical effects; as long as the usage requirements are met, they are all within the protection scope of the present invention.

Claims

1. A super weather-resistant anti-corrosion coating for the outer wall of a tower, comprising component A and component B, characterized in that: Component B is a curing agent, and the mass ratio of component A is: The composition includes: 5-8 parts of polysiloxane-modified epoxy resin, 45-50 parts of epoxy resin, 5-8 parts of oil-soluble phenolic resin, 5-6 parts of hexamethoxymethyl melamine resin, 8-10 parts of rutile titanium dioxide, 10-15 parts of mica iron oxide, 3-5 parts of polydopamine-modified precipitated barium sulfate, 0.5-1 part of ultraviolet absorber, 0.3-0.8 parts of leveling agent, 0.2-0.5 parts of defoamer, 1-2 parts of dispersant, and 12-17 parts of solvent.

2. The ultra-weather-resistant anti-corrosion coating for the outer wall of a tower according to claim 1, characterized in that: The mass ratio of component A to component B is 5-7:

1.

3. The ultra-weather-resistant anti-corrosion coating for the outer wall of a tower according to claim 1, characterized in that: The polysiloxane-modified epoxy resin is obtained by catalytic modification using E-44 epoxy resin as a base and hydroxyl-terminated polydimethylsiloxane as a modifier.

4. The ultra-weather-resistant anti-corrosion coating for the outer wall of a tower according to claim 1, characterized in that: The epoxy resin used is E-44 epoxy resin.

5. The ultra-weather-resistant anti-corrosion coating for the outer wall of a tower according to claim 1, characterized in that: The rutile titanium dioxide has a particle size of 0.2-0.3 μm.

6. The ultra-weather-resistant anti-corrosion coating for the outer wall of a tower according to claim 1, characterized in that: The polydopamine-modified precipitated barium sulfate is polydopamine-encapsulated precipitated barium sulfate.

7. The ultra-weather-resistant anti-corrosion coating for the outer wall of a tower according to claim 6, characterized in that: The polydopamine-modified precipitated barium sulfate has a core of precipitated barium sulfate and a surface coating of polydopamine, forming a core-shell structure.

8. The ultra-weather-resistant anti-corrosion coating for the outer wall of a tower according to claim 1, characterized in that: The ultraviolet absorber is UV327; The leveling agent is BYK-333; The defoamer is BYK-066; The dispersant is BYK-110; The solvent is composed of xylene and n-butanol, and the mass ratio of xylene to n-butanol is 7:

3.

9. The ultra-weather-resistant anti-corrosion coating for the outer wall of a tower according to claim 1, characterized in that: The curing agent is isophorone diamine.

10. The ultra-weather-resistant anti-corrosion coating for the outer wall of a tower according to claim 1, characterized in that: The preparation method of the ultra-weather-resistant anti-corrosion coating includes the following steps: Step 1: Add polysiloxane-modified epoxy resin, epoxy resin, oil-soluble phenolic resin, and hexamethoxymethyl melamine resin to a mixed solvent and stir until homogeneous. Then, add rutile titanium dioxide, mica iron oxide, and polydopamine-modified precipitated barium sulfate sequentially and stir continuously for 20 minutes. Finally, add ultraviolet absorber, leveling agent, defoamer, and dispersant and disperse for 30-40 minutes to obtain component A mixture. The stirring speed for homogeneous mixing is 400-600 r / min, the stirring speed for continuous stirring is 700-1000 r / min, and the stirring speed for dispersion is 1000-1500 r / min. Step 2: Rapidly stir the mixture of component B and component A in a certain proportion to obtain an ultra-weather-resistant and corrosion-resistant coating; the stirring speed of the rapid stirring is 1500-2000 r / min.